Penerapan Design Thinking dalam Perancangan Prototipe Sistem Informasi Online Food Delivery - Marsha Febriani Aditama; Umi Mamnuah Al Amini; Indah Fajriah; Jihan Cahya Marsya (Prosiding SISFOTEK, 2025)
In this project, a mobile-based food delivery information system prototype was designed using the Design Thinking methodology. The development of a user-oriented prototype design aimed to address a number of issues in related applications, including ambiguous user interfaces, limited accessibility, and challenging navigation. The five main stages of Design Thinking—empathy, definition, ideation, prototyping, and testing—were used to carry out the development process. To determine user needs and assess satisfaction levels after prototype testing, 20 respondents were given pre-test and post-test questionnaires. Based on the test results, the prototype design was able to meet most user needs related to usability, interface appearance, and application functionality, with an average Likert score of 4.123, which falls into the “Good” category. These results demonstrate the effectiveness of the Design Thinking methodology in creating user-friendly and intuitive mobile applications. It is hoped that this will meet the needs of communities in areas with limited access to digital services